2013
DOI: 10.1111/jawr.12131
|View full text |Cite
|
Sign up to set email alerts
|

Creating False Images: Stream Restoration in an Urban Setting

Abstract: Stream restoration has become a multibillion dollar business with mixed results as to its efficacy. This case study utilizes pre‐ and post‐monitoring data from restoration projects on an urban stream to assess how well stream conditions, publicly stated project goals, and project implementation align. Our research confirms previous studies showing little communication among academic researchers and restoration practitioners as well as provides further evidence that restoration efforts tend to focus on small‐sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 51 publications
(87 reference statements)
0
34
0
1
Order By: Relevance
“…The intent of restoration is to return the stream to some predisturbance condition, but the practitioners of urban stream restoration typically accept that regaining all structural and functional components of the predisturbance condition is unlikely (Booth 2005, Cockerill andAnderson 2014). Many project managers seek to remedy only specific issues (e.g., erosion, flooding) rather than the multiple issues needed for long-term structural and functional change (Palmer et al 2014).…”
Section: Reference-condition Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…The intent of restoration is to return the stream to some predisturbance condition, but the practitioners of urban stream restoration typically accept that regaining all structural and functional components of the predisturbance condition is unlikely (Booth 2005, Cockerill andAnderson 2014). Many project managers seek to remedy only specific issues (e.g., erosion, flooding) rather than the multiple issues needed for long-term structural and functional change (Palmer et al 2014).…”
Section: Reference-condition Approachmentioning
confidence: 99%
“…The temporal and spatial scales of restoration projects often are misaligned with the temporal and spatial scales of the causes of impairment (National Research Council 1999, Wohl et al 2005, Naiman 2013, Cockerill and Anderson 2014. Reach-scale restoration projects are unlikely to affect water quality, the frequency of disturbance, or other functional or structural components of the stream system when human modifications to catchment landscapes are causing impairment Vietz 2016, Walsh et al 2016).…”
Section: Mismatch Between Temporal and Spatial Scale Of Effects And Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Success of such schemes has been mixed (Cockerill and Anderson, 2014), as increased habitat heterogeneity does not necessarily promote biodiversity (Palmer et al, 2010), especially when wider pressures such as hydrological alteration and water pollution prevail (Hughes et al, 2014a). This reflects a wider lack of knowledge of process-based river restoration (Palmer et al, 2014), which is exacerbated by a profound lack of post-project monitoring.…”
Section: Restoration Of Urban Aquatic Ecosystemsmentioning
confidence: 99%
“…However, these are not always complementary and an analysis of the impacts of increased floodplain connectivity in Vienna, Austria, demonstrated that proposed measures would provide ecological benefits, but with tradeoffs in ecosystem service provision (Sanon et al, 2012). Conversely, Cockerill and Anderson (2014) identified that stream restoration for societal benefits (aesthetics, erosion control, protection of infrastructure) provided little wider environmental benefit.…”
Section: Restoration Of Urban Aquatic Ecosystemsmentioning
confidence: 99%